Physiology Drives Reworking of Amino Acid δ2H and δ13C in Butterfly Tissues - Morra, Kaycee E.; Newsome, Seth D.; Graves, Gary R.; Fogel, Marilyn L. (Frontiers in Ecology and Evolution, 2021)
Studies of animal movement and migration over large geospatial scales have long relied on natural continental-scale hydrogen isotope (δ2H) gradients in precipitation, yet the physiological processes that govern incorporation of δ2H from precipitation into plant and then herbivore tissues remain poorly understood, especially at the molecular level. Establishing a biochemical framework for the propagation of δ2H through food webs would enable us to resolve more complicated regional-scale animal movements and potentially unlock new applications for δ2H data in animal ecology and eco-physiology. Amino acid δ2H analysis offers a promising new avenue by which to establish this framework. We report bulk tissue δ2H, δ13C, and δ15N data as well as amino acid δ2H and δ13C data from three Pipevine swallowtail (Battus philenor) tissues—caterpillars, butterfly bodies, and wings—as well as their obligate plant source: pipevine leaves (Aristolochia macrophylla). Insects are often dominant herbivores in terrestrial food webs and a major food source for many higher-level consumers, so it is particularly important to understand the mechanisms that influence insect tissue δ2H values. Our data reveal extensive δ2H variation within and among individuals of a relatively simple plant-herbivore system that cannot be explained by temporal or geospatial gradients of precipitation δ2H or dietary differences. Variations in essential amino acid δ2H and δ13C indicate that B. philenor acquire these compounds from an additional source that is isotopically distinct from pipevine leaves, potentially gut microbes. We also found multiple isotopic carryover effects associated with metamorphosis. This study emphasizes the strong influence of physiology on consumer-diet δ2H discrimination in a local population of pipevines and swallowtails and provides a template that can be broadly applied to Lepidoptera—the second most diverse insect order—and other holometabolous insects. Understanding these physiological mechanisms is critical to interpreting the large degree of δ2H variation in consumer tissues often observed at a single collection site, which has implications for using δ2H isoscapes to study animal movement. Further investigation into amino acid δ2H holds promise to elucidate how subsets of amino acids may be best utilized to address specific ecological and physiological questions for which bulk tissue δ2H is insufficient.